EDUCOLOGYCAL TRAINING IN ENSURING THE QUALITY OF EDUCATION AT THE UNIVERSITY - Olena Protsenko; Olga Melnychenko (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article is devoted to the analysis of the content of educologycal training in the educational programs «Preschool Education», «Primary Education», «Management of Educational Institutions» full-time and part-time at Borys Grinchenko Kyiv University, which involves studying the interdisciplinary course «Educology». The article emphasizes the contribution of educology as a scientific phenomenon in ensuring the quality of university education due to its integrated and interdisciplinary nature. A significant difference between the object of study of education and other humanities is that educology is a kind of educational synergy for the study of education, which generates a systematic set of educational sciences such as philosophy of education, history of education, educational policy, educational law, education management, economics of education, sociology of education, culturology of education. The authors analyzed the effectiveness of teaching the discipline «Educology» on the basis of a survey of undergraduates of the university, in which special attention was paid to the development of critical thinking; awareness of patterns, trends, sources of education and educational systems; application of a synergetic approach in education management; formation of the ability to find means of solving current problems in the field of education; understanding of education as a specific sector of the economy, mechanisms of competitiveness of educational institutions, understanding of education as a social institution, the role of legal aspects in the development of education, etc. It is proved that the study of the course «Educology» will contribute to the development of future professionals in the field of education skills to systematically solve the multifaceted problem of ensuring the quality of education at the university; consider prospects and forecast changes to improve it.